Identity and Piety: Critical Discourse Analysis on Indonesian Ulema Council’s Fatwa about The Law Using Non-Moslim Religious Attributes - Subuki, Makyun; Akmal, Hilmi; Hudaa, Syihaabul (AHKAM : Jurnal Ilmu Syariah, 2023)
In December 2016, shortly after the Action to Defend Islam 212 was held, the Indonesian Ulema Council published a fatwa on the Law Using Non-Muslim Religious Attributes. This fatwa reaped controversy because it was followed by sweeping action by a number of mass organizations against the Christmas attribute. Since this fatwa caused controversy, this study sought to examine it with a critical discourse analysis approach. This study covers three dimensions of the fatwa: the textual dimension, the dimension of discursive practice, and the dimensions of social practice. Based on the analysis that has been carried out, this study has three findings. First, linguistic analysis of this fatwa  showed  that  the  fatwa  is  an  ideological  text.  Furthermore,  this  fatwa has intertextuality with other texts, namely the opinions of previous ulemas, which also prohibit the use of religious attributes of non-Muslims. Second, as a discursive practice, this fatwa affirms the view of several religious mass organizations that not only forbid wearing religious attributes of non-Muslims but also at the same time justified their attitude in sweeping against the religious attributes  of  non-Muslims,  for  example,  Islamic  Front  Defense  (FPI)  and Klaten Islamic Paramilitaries (LAKIK). Third, situationally and institutionally, this  fatwa  is  possible  to  be  issued  not  only  because  of  the  encouragement of several mass organizations that consider that using religious attributes of non-Muslims is haram but also because of the influence of consolidation of these mass organizations, which rich their peak level after the series of Action to Defend Islam. Lastly, a value system that views identity as permanent and unchanging in Indonesian Muslim society is still very dominant, so it is also determining the issuance of this fatwa.  Pada  bulan  Desember  2016,  tak  lama  setelah  Aksi  Bela  Islam  212 digelar, Majelis Ulama Indonesia menerbitkan fatwa tentang Hukum Penggunaan Atribut Keagamaan Non-Muslim. Fatwa ini menuai kontroversi karena disusul aksi sapu bersih sejumlah ormas yang menentang atribut Natal. Karena fatwa ini menimbulkan kontroversi, maka penelitian ini berupaya mengkajinya dengan pendekatan  analisis  wacana  kritis.  Kajian  ini  mencakup  tiga  dimensi  fatwa: dimensi  tekstual,  dimensi  praktik  kewacanaan,  dan  dimensi  praktik  sosial. Berdasarkan analisis yang telah dilakukan, penelitian ini mempunyai tiga temuan. Pertama,  analisis  kebahasaan  fatwa  ini  menunjukkan  bahwa  fatwa  tersebut merupakan  teks  ideologis.  Lebih  lanjut,  fatwa  ini  memiliki  intertekstualitas dengan  nash  lain,  yaitu  pendapat  para  ulama  terdahulu  yang  juga  melarang penggunaan atribut agama non-Muslim. Kedua, sebagai praktik diskursif, fatwa ini mengafirmasi pandangan beberapa ormas keagamaan yang tidak hanya melarang pemakaian  atribut  keagamaan  non-Muslim  namun  sekaligus  mem sikapnya dalam melakukan penyisiran terhadap atribut keagamaan non-Muslim, mislanya Front Pembela Islam (FPI) dan Laskar Islam Klaten (LAKIK). Ketiga, secara situasional dan institusional, fatwa ini dimungkinkan dikeluarkan bukan hanya  karena  dorongan  dari  beberapa  ormas  yang  menganggap  penggunaan atribut keagamaan non-Muslim haram, namun juga karena pengaruh konsolidasi ormas-ormas  tersebut,  yang  besar  di  mana  puncaknya  setelah  rangkaian  Aksi Bela  Islam.  Terakhir,  sistem  nilai  yang  memandang  identitas  sebagai  sesuatu yang  permanen  dan  tidak  berubah  dalam  masyarakat  Islam  Indonesia  masih sangat dominan sehingga ikut menentukan dikeluarkannya fatwa ini.